TURTLES: THE THREATS, THE CONSERVATION PRACTICES AND THE COMMUNITY EXPECTATIONS IN MUBRANI DISTRICT TAMBRAUW REGENCY - Taran, Denisa Melanesia Kreglika; Sawaki, Saremay Max Romario (ZOO INDONESIA, 2023)
Along the coastal area of Mubrani District is turtle spawning ground. The spawning season is once a year, which is in April. This study aims to identify threats to turtles, conservation efforts applied by the community and the community expectations in improving conservation programs that have been carried out. This research was conducted in Mubrani District by interviewing 45 people in five villages, which are directly adjacent to the coastal area, namely Wasnembri, Atori, Bonpaya, Bawei and Beriambeker. Determination of respondents used random sampling technique. Based on the interview, it is known that there are three species of turtles who own the spawning ground in the five villages, which are Chelonia mydas, Dermochelys coriacea and Eretmochelys imbricata. The threats to turtles in these areas are poaching, the utilization of turtles mainly as a source of protein and a source of income by the local communities and predatory animal of turtle eggs. There are three conservation efforts formulated by the communities, namely prohibition of people from outside the villages to access the beach at the time of spawning to hatching, communities who hunt turtles and their eggs must share their catches with neighbours and or relatives and camouflage of turtle nests. Furthermore, the community expects to improve the current conservation actions by the establishment of monitoring post and daily patrols by field officers from the Natural Resources Conservation Division of West Papua Province at the time of spawning to hatching, clarity of regulations and sanctions for poachers and the reciprocity of the prohibition on the utilization of turtles imposed by the government, which are the community involvement as turtle monitoring officers employed directly by the Natural Resources Conservation Division of West Papua Province and turtle tourism development by the government of Tambrauw Regency.